Association Between Ultrasound Parameters and History of Ischemic or Hemorrhagic Stroke in Patients With Moyamoya Disease - Zheng, Shuai; Ge, Peicong; Li, Yi; Wang, Jingzhe; Shi, Zhiyong; Zhang, Jinghan; He, Lei; Cheng, Linggang; Zhang, Dong; He, Wen (Frontiers in Neurology, 2021)
Objective: To explore the association between ultrasound parameters and stroke in patients with moyamoya disease (MMD) and develop an ultrasound-based nomogram to identify stroke in patients with MMD. Methods: We prospectively enrolled 52 consecutive patients (92 hemispheres) with MMD at the Beijing Tiantan Hospital. Thirty-six patients (65 hemispheres) were assigned to the training dataset from September 2019 to February 2020, and 16 patients (27 hemispheres) were assigned to the validation dataset from March 2020 to July 2020. Multivariate logistic regression analysis was applied to identify ultrasound parameters associated with ipsilateral stroke in patients with MMD, and a nomogram was subsequently constructed to identify stroke in patients with MMD. The performance of the nomogram was evaluated with respect to discrimination, calibration, and clinical usefulness. Results: Multivariate analysis indicated that the flow volume (FV) of the extracranial internal carotid artery (EICA) and the peak systolic velocity (PSV) of the posterior cerebral artery (PCA) were independently associated with ipsilateral stroke in patients with MMD, a nomogram incorporating these two parameters was constructed to identify stroke patients. The area under the receiver operating characteristic (AUROC) curves was 0.776 (95% CI, 0.656-0.870) in the training dataset and 0.753 (95% CI, 0.550-0.897) in the validation dataset suggested that the model had good discrimination ability. The calibration plot showed good agreement in both the two datasets. The decision curve analysis (DCA) revealed that the nomogram was clinically useful. Conclusions: Ultrasound parameters of EICA and PCA are independently associated with ipsilateral stroke in patients with MMD. The ultrasound-based nomogram might provide information to identify MMD patients with high risk of stroke, future long-term follow-up studies are needed to prove the predictive value in other independent cohorts.